2018
DOI: 10.21613/gorm.2017.713
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Alterations of Hormone Profile Following Oocyte Pick-Up in Women with Polycystic Ovarian Syndrome to Assess the Effect of Multiple Needle Entries Into the Ovarian Cortex and Stroma

Abstract: <p><strong>Objective:</strong> Some hormonal alterations after ovarian diathermy have been proposed in previous studies. Based on this data, we aimed to analyze some hormone profile changes following oocyte pick-up in women with polycystic ovarian syndrome.<br /><strong></strong></p><p><strong>Study Designs:</strong> A total of 50 women with polycystic ovarian syndrome underwent ovarian stimulation for IVF cycle with an indication of anovulatory infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the literature some studies suggested that transvaginal approach is preferred as the gold standard method for oocyte retrieval due to shorter operation time and less invasiveness, but the transabdominal approach is also considered a safe and efficacious procedure. [16][17][18] Mean duration of the procedure was 12.4 AE 1.2 min, which was quite comparable to standard vaginal oocyte retrieval procedure. For further analysis, we have started a retrospective study to compare the main outcome measures between conventional transvaginal follicle aspiration and TUGOR in terms of total number of collected oocytes and mature oocytes, oocyte collection rates, complication rates, duration of the procedure and patient tolerability.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the literature some studies suggested that transvaginal approach is preferred as the gold standard method for oocyte retrieval due to shorter operation time and less invasiveness, but the transabdominal approach is also considered a safe and efficacious procedure. [16][17][18] Mean duration of the procedure was 12.4 AE 1.2 min, which was quite comparable to standard vaginal oocyte retrieval procedure. For further analysis, we have started a retrospective study to compare the main outcome measures between conventional transvaginal follicle aspiration and TUGOR in terms of total number of collected oocytes and mature oocytes, oocyte collection rates, complication rates, duration of the procedure and patient tolerability.…”
Section: Discussionmentioning
confidence: 74%
“…In the literature some studies suggested that transvaginal approach is preferred as the gold standard method for oocyte retrieval due to shorter operation time and less invasiveness, but the transabdominal approach is also considered a safe and efficacious procedure 16–18 . Mean duration of the procedure was 12.4 ± 1.2 min, which was quite comparable to standard vaginal oocyte retrieval procedure.…”
Section: Discussionmentioning
confidence: 90%